2009
DOI: 10.1097/iae.0b013e3181a2c1eb
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of in-Office Diagnostic Vitreous Sampling in Patients With Vitreoretinal Pathology

Abstract: This prospective study has shown that in-office vitreous sampling of 50 microL to 100 microL is a safe and reproducible procedure. Larger randomized studies will be helpful to further assess the safety and long-term effects of in-office diagnostic vitreous sampling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“… 2 , 7 , 10 , 20 , 21 Office-based aspiration of vitreous sample for proteomic analysis has less commonly been used. 27 Despite theoretical risks of vitreoretinal traction, a large review of in-office vitreous sampling by Pfahler et al 18 showed that aspiration of small volumes was a safe and reproducible procedure. Lobo and Lightman 28 reported a similar rate, 92%, of obtaining adequate sample from vitreous aspiration and few complications in diagnosing patients with infectious, malignant, and inflammatory causes of uveitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 , 7 , 10 , 20 , 21 Office-based aspiration of vitreous sample for proteomic analysis has less commonly been used. 27 Despite theoretical risks of vitreoretinal traction, a large review of in-office vitreous sampling by Pfahler et al 18 showed that aspiration of small volumes was a safe and reproducible procedure. Lobo and Lightman 28 reported a similar rate, 92%, of obtaining adequate sample from vitreous aspiration and few complications in diagnosing patients with infectious, malignant, and inflammatory causes of uveitis.…”
Section: Discussionmentioning
confidence: 99%
“…Giansanti et al 17 reported that microsampling of small volumes (10–15 μL) in rabbit eyes is a useful technique in vitreous pharmacokinetic studies. Pfahler et al 18 found very few complications with a large number of in-office vitreous sampling attempts, but did not report on the ability to analyze samples acquired in this manner.…”
mentioning
confidence: 99%
“…1A ). 20 , 21 We reported that needle biopsies are comparable to vitreous cutter biopsies. 14 A prospective case series of patients undergoing this office-based aspiration demonstrated the method to be reproducible and safe with an average of 100 to 200 μL undiluted vitreous obtained in 88% of patients.…”
Section: Liquid Biopsy Techniques For Ophthalmic Tissuesmentioning
confidence: 94%
“…A study of 578 in-office vitreous aspiration procedures demonstrated that this technique is safe and reproducible with a high yield of successful samples (95%) [70]. Vitreous sampling does not expose the patient to additional office visits or setup, and it can be performed prior to intravitreal injection.…”
Section: Treatment Of Diabetic Retinopathymentioning
confidence: 99%